Medical care for transgender individuals at a hospital in southern Brazil: why do they drop out from our service? - Guadagnin, Fernanda; Schwarz, Karine; Cardoso da Silva, Dhiordan; Salati, Leonardo Romeira; Kayser, Vinicius; Lobato, Maria Inês Rodrigues (Frontiers in Public Health, 2024)
Objective: The objective of the study was to investigate dropout rates and discern potential factors contributing to the discontinuation of treatment provided to transgender individuals by the Transdisciplinary Gender Identity Program at the Hospital de Clínicas de Porto Alegre (PROTIG). Methodology: This study employs a descriptive, cross-sectional, retrospective design to analyze socio-demographic and clinical data obtained from medical records of patients treated at PROTIG between 2000 and 2018. A structured form, devised by PROTIG's professional team, was utilized to extract and evaluate several variables including: age, gender, education level, diagnosis of F64 according to the International Classification of Diseases (ICD-10: Version: 2010), clinical comorbidities (coded by ICD-10), laboratory diagnosis of sexually transmitted infections, distance between patients' residence and the hospital, and year of entry into PROTIG. The patient cohort was stratified into two categories based on their duration of attendance: dropout (defined as attendance for up to 365 days) and non-dropout (attendance exceeding 365 days). Categorical variables between dropout and non-dropout groups were compared using Pearson's chi-square test.Additionally, Poisson regression analysis was utilized, employing a 95% confidence interval (CI) and setting the significance level at 0.05.The study included a total of 888 patients accessing PROTIG, with 275 (31%) classified in the dropout group. Of the patient population, 65.5% (n=582) self-identified as transgender women, while 34.5% (n=306) identified as transgender men. Significant differences were noted between the dropout and non-dropout groups. Specifically, differences were noted among transgender women (p< 0.001), individuals with lower levels of education (p<0.001), those with fewer diagnoses classified under ICD-10 as F64 (p<0.001), individuals exhibiting fewer clinical comorbidities recorded in ICD-10 (p<0.001), and those who commenced inclusion in PROTIG after 2010 (p<0.001).There exists a notable rate of treatment discontinuation among individuals receiving care at PROTIG, with statistically significant variances observed between groups. We posit potential rationales for this discontinuation, informed by care experiences and feedback from group attendees: Increased accessibility to outpatient services in our jurisdiction for Transgender Care, along with heightened societal awareness of gender identity fostering diverse gender expression avenues devoid of reliance on gender-affirming surgical interventions.